Detection of JAK2 V617F Mutation among Donors with Erythrocytosis / Siti Fatimah Mohamed Kamaruzzaman … [et al.] - Mohamed Kamaruzzaman, Siti Fatimah; Mohd Noor, Noor Haslina; Mohd Yusoff, Shafini; Abdullah, Wan Zaidah; Hasan, Mohd Nazri (Universiti Teknologi MARA Cawangan Selangor, 2018)
Introduction: It is mandatory that every blood donor must have their haemoglobin (Hb) values measured before blood donation. High Hb may indicate an underlying hidden pathological condition. The aim of this study is to investigate the occurrence of the JAK2 V617F gene mutation in blood donors with erythrocytosis. Methods: A cross-sectional study was conducted over a nine-month period involving blood donors with high pre-donation Hb. A total of 45 blood donors with total white cell (TWC) > 12.0x 109/l, platelet > 450x109/ l and Hb > 18g/dL were subjected to JAK2 V617F gene mutation analysis. Samples were collected and analysed for haematological tests and detection of JAK2 V617F mutation. Results: From a total of 2238 blood donors, 175 blood donors had high haemoglobin value. Samples from forty-five of these donors were then analysed for JAK2 V617F using allele-specific polymerase chain reaction (PCR). The prevalence of blood donors with erythrocytosis was 7.8%. All samples were negative for the JAK2 V617F mutation. Conclusions: Erythrocytosis can be relative or absolute and the different causes can be distinguished on the basis of clinical signs and symptoms. An absence of the JAK2 V617F mutation cannot by itself excludes the diagnosis of polycyhaemia vera (PV) since erythrocytosis is the single clinical feature that sets PV apart from other types of myeloproliferative neoplasm (MPN). Further study is required for the detection of other gene mutations that activates the JAK-STAT signalling pathway that could be identified in JAK2 V617F-negative MPN patients.